2022
DOI: 10.23975/bjvetr.2022.177425
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Orf virus in sheep in Basrah province, Southern Iraq

Abstract: Orf which is commonly referred to as contagious ecthyma is a viral infectious disease that infects small ruminants. Little is known about the disease status in our geographical region. This study aimed to determine the seroprevalence of Orf virus in sheep in Basrah province, southern Iraq. Serum samples were randomly collected from 380 sheep of different age and sex groups from 4 different regions in Basrah province, which were Zubair, Abulkhasib, Shatt Al-Arab, and Qurnah. The samples were tested by ELISA for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This is done to prevent a rise in RT in homoeothermic animals, such as sheep (Singh et al 2016). The increase in HR in Awassi in our study was also documented by (Al-Azzawi et al 2017), which revealed that the HR of local Awassi was lower than that of Turkish Awassi. A possible explanation may be that more heat was dissipated through the skin as a result of increased circulation from the heart and lungs.…”
Section: Physiology Responsesupporting
confidence: 69%
“…This is done to prevent a rise in RT in homoeothermic animals, such as sheep (Singh et al 2016). The increase in HR in Awassi in our study was also documented by (Al-Azzawi et al 2017), which revealed that the HR of local Awassi was lower than that of Turkish Awassi. A possible explanation may be that more heat was dissipated through the skin as a result of increased circulation from the heart and lungs.…”
Section: Physiology Responsesupporting
confidence: 69%
“…The prevalence rate in sheep aged 1-6 months was significantly higher than that of the other age groups. Lambs have a higher probability of infection than adults because lambs' immune system is still underdeveloped and depends mostly on innate immunity and maternal antibodies to protect against the Orf virus [14]. The result of this study was detected the high sero-prevalence of Orf virus IgM (73.63%) and IgG (89%) among the lamb with or without clinical signs of Orf virus infection.…”
Section: Discussionmentioning
confidence: 71%
“…Then the inoculated eggs are incubated for 4-7 days or until the embryos die. After that, the allantois fluids harvested are tested with a hemagglutination activity (HA) test using chicken RBCs (15,16). Carrying out HA assay only is insufficient to correctly identify the PPMV-1, as all avian paramyxoviruses serotypes and avian influenza viruses (AI) show hemagglutination activity.…”
Section: Diagnosis Of Ppmv-1 Infectionmentioning
confidence: 99%